Implementation of micro-level problem based learning in a course on electronic materials - Haseeb, A.S. Md. Abdul (International Council on Materials Education, 2011)
Accreditation bodies for engineering education around the world have been advocating for the implementation of outcome based education. In order to achieve this effectively, engineering educators are increasingly adopting student-centered modes of learning. One such mode is problem based learning (PBL). In this paper experience with the implementation of micro-level PBL is described. Here one topic in a course on electronic materials at the undergraduate programme in materials engineering is taught using PBL. At the end of the course, students feedback is recorded to gauge the success or otherwise of this learning method. In general, student are found to be more enthuiastic in learning with PBL than in lectures. They appreciated to have, in the PBL, an opportunity to play the role of a professional engineer and to apply acquired kowledge to solve a particular problem. Student feedback reveals that PBL can be effective in achieving the programme outcomes (POs) that are not easy to achieve through lectures, such as those related to i) lifelong learning, ii) team work, iii) professional and ethical responsibility, iv) economic, social and environmental impact, etc.. Thus PBL can complement lectures in successfully implementing outcome based education. Implementation of PBL at the micro level, that is, for one topic in a course has been found to be fairly easy as it does not require any extra resources. Since converting the whole undergraduate programme into PBL can be a formidable venture, it is believed that PBL can be adopted for a limited number of topics in some of the major courses in the programme with tangible benefits.